2012
DOI: 10.2141/jpsa.011079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cultures of <I>Aspergillus oryzae </I>on Inflammatory Response and mRNA Expression in Intestinal Immune-Related Mediators of Male Broiler Chicks

Abstract: Effect of Aspergillus oryzae (CAO) culture on systemic inflammatory response and mRNA expression of immune-related mediators in intestine was studied in male broiler chicks. Feeding CAO alleviated enhancement of early inflammatory response such as changes in acute phase substance and growth performance during immunological stress induced by lipopolysaccharide and Sephadex. Furthermore, changes in mRNA expression of immune-related mediators in the upper and lower intestine at 5 and 14 days of age were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…The immunomodulatory function of Aspergillus spp. has been also confirmed by many studies in other vertebrates (Abu Hafsa et al, 2016; El‐Deep et al, 2021; Saleh et al, 2017; Takahashi, 2012; Zamanizadeh et al, 2021).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The immunomodulatory function of Aspergillus spp. has been also confirmed by many studies in other vertebrates (Abu Hafsa et al, 2016; El‐Deep et al, 2021; Saleh et al, 2017; Takahashi, 2012; Zamanizadeh et al, 2021).…”
Section: Discussionsupporting
confidence: 61%
“…Neutrophils are one of the first immune components to respond to inflammation (Ellis, 1999). In vertebrates (Abu Hafsa et al, 2016;El-Deep et al, 2021;Saleh et al, 2017;Takahashi, 2012;Zamanizadeh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines such as IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) originated from macrophages were the major cellular messengers initiating metabolic cascade alterations following the innate immune response ( Jiang et al., 2015 ). Lipopolysaccharide was demonstrated to increase pro-inflammatory cytokines secretion and suppress animal growth ( Takahashi, 2012 , Tan et al., 2014 , Li et al., 2015b ). Results of the present study results showed that serum IL-1β, IL-6 levels of broilers significantly increased after LPS injection, and then were gradually back to the previous level, which indicated that broilers began to adapt immunological stress and metabolic function gradually recovered to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the European Union and some other countries have forbidden the use of antibiotics in livestock feed according to consideration of antibiotics resistance causing negative effects on human health ( Huyghebaert et al., 2011 ). It is reported that regulation of immune system in birds by certain nutrients or antibiotic-free substances appears to be a way to avoid or lower use of antibiotics ( Takahashi, 2012 ). Therefore, development of safe and effective nutritional additives to modulate the immune function is of great significance to protect chickens from immune stress ( Liu et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide causes oxidative stress and promotes inflammatory reactions ( Rosadini and Kagan, 2017 ). It has been shown to increase the secretion of proinflammatory cytokines and inhibit animal growth ( Takahashi, 2012 ; Tan et al, 2014 ; Li et al, 2015 ). Our results revealed that LPS stimulation significantly increased serum inflammatory cytokines TNF-α, IL-1β, and IL-6, and reduced the concentration of anti-inflammatory cytokine IL-10 at both time intervals.…”
Section: Discussionmentioning
confidence: 99%